Photophysical, photochemical and BSA binding/BQ quenching properties of quaternizable coumarin containing water soluble zinc phthalocyanine complexes - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The non-peripherally (np-QZnPc) and peripherally (p-QZnPc) tetrakis-[7-oxo-(3-[(2-diethylaminomethyliodide)ethyl)]-4-methylcoumarin]-Phthalocyaninatozinc complexes have been prepared by quaternization of non-peripherally and peripherally tetrakis[7-oxo-(3-[(2-diethylamino)ethyl)]-methylcoumarin] phthalocyaninato zinc complexes with methyliodide in dimethylsulfoxide (DMSO). The new quaternized zinc phthalocyanine complex (np-QZnPc) has been characterized by elementel analysis, MALDI-TOF, IR and UV-vis spectral data. The photophysical and photochemical properties of the peripherally and non-peripherally quaternized tetrakis-3-[(2-diethylamino)ethyl]-7-oxo-4-methylcoumarin substituted zinc phthalocyanines are reported. The effects of the position of the substituents and the aggregation of the phthalocyanine molecules on the photophysical and photochemical properties are also investigated. General trends are described for photodegradation, singlet oxygen and fluorescence quantum yields, and fluorescence lifetimes for complexes np-ZnPc/p-ZnPc in DMSO and for complexes np-QZnPc/p-QZnPc in DMSO, phosphate buffered solution (PBS) and PBS+Triton-X 100 solutions. The fluorescence of the tetra-substituted quaternized zinc phthalocyanine complexes (np-QZnPc/p-QZnPc) are effectively quenched addition of 1,4-benzoquinone (BQ) and this study also presented the ionic zinc phthalocyanine complexes strongly bind to bovine serum albumin (BSA). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Coumarin (2H-chromen-2-one); Phthalocyanine; Fluorescence; Quaternization; Singlet oxygen; Quantum yield; METAL PHTHALOCYANINES; QUANTUM YIELDS; FLUORESCENCE; OXYGEN; PHOTOSENSITIZERS; SUBSTITUENTS; AGGREGATION; DERIVATIVES; BEARING